The psychosomatic disorders in children and adolescents - Isabel María Sánchez Boris (Centro Provincial de Información de Ciencias Médicas, 2020)
The psychosomatic disorders are characterized by somatic signs of non-pathological origin which possess a significant prevalence in children and adolescents; however, it is difficult to identify them, because there is no appropriate consent for its diagnosis and the investigations about the topic are insufficient. That is the reason why we decided to carry out the present work, in which some etiopathogenic, clinical and epidemiological aspects are approached that provide the main elements to identify these disorders and to establish a good diagnosis; it is also relevant that these disorders are frequent in juvenile populations with introversion features and/or personal and family history of physical and mental diseases, with multifactorial cause, although among the many relevant factors we can mention vulnerability to stress, family dysfunction, parental overprotection, as well as the precipitant situations (school harassment, parents' separation, sexual abuse) and the permanent situations; the latter are conditioned by the primary and secondary benefits that  minors obtain with these sufferings.